ChemInform Abstract: One‐Step Synthesis of Dicarboxamides Through Pd‐Catalyzed Aminocarbonylation with Diamines as N‐Nucleophiles. Issue 28 (July 2015) - Carrilho, Rui M. B.; Almeida, Ana R.; Kiss, Mercedesz; Kollar, Laszlo; Skoda‐Foeldes, Rita; Dabrowski, Janusz M.; Moreno, Maria Jose S. M.; Pereira, Mariette M.
Abstract A versatile and atom‐economical route to alkenyl and aryl dicarboxamides by catalytic aminocarbonylation is described.